The judicial career in the Peruvian model - Vinatea Medina, Ricardo Guillermo (2020)
Starting from the hypothesis that in Peru does not exist the Judicial career itself, it is necessary to begin a study of the current nationallegislation, antecedents and projects, to display a vision of how it is developed in different countries. Finalizes with some proposals thatshould be consider un future laws on this affair.